2018
DOI: 10.1101/504043
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The human HELLS chromatin remodelling protein promotes end resection to facilitate homologous recombination within heterochromatin

Abstract: Efficient double-strand break repair in eukaryotes requires manipulation of chromatin structure. ATP-dependent chromatin remodelling enzymes can facilitate different DNA repair pathways, during different stages of the cell cycle and in a range of chromatin environments. The contribution of remodelling factors to break repair within heterochromatin during G2 is unclear. The human HELLS protein is a Snf2-like chromatin remodeller family member and is mutated or misregulated in several cancers and some cases of I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…3G) were downregulated in mHSPCs, suggesting a decrease in proliferation (Shinya et al, 2014;Snyder et al, 2005) consistent with the cytopenic phenotype noted at 6mpf. In addition we noted a decrease in genes required for DNA repair and genome stability, such as hells (Kollárovič et al, 2020), npm1a (Grisendi et al, 2005;Koike et al, 2010) and ncl (Kawamura et al, 2019;Scott and Oeffinger, 2016) (Fig. 3G).…”
Section: Whenmentioning
confidence: 83%
“…3G) were downregulated in mHSPCs, suggesting a decrease in proliferation (Shinya et al, 2014;Snyder et al, 2005) consistent with the cytopenic phenotype noted at 6mpf. In addition we noted a decrease in genes required for DNA repair and genome stability, such as hells (Kollárovič et al, 2020), npm1a (Grisendi et al, 2005;Koike et al, 2010) and ncl (Kawamura et al, 2019;Scott and Oeffinger, 2016) (Fig. 3G).…”
Section: Whenmentioning
confidence: 83%
“…For example, the chromatin-binding protein Lens epithelium-derived growth factor (LEDGF) binds preferentially to epigenetic methyl-lysine histone markers characteristic of active transcription and also interacts with CtIP in a damage dependent way, thereby improving resection within active genomic regions (Daugaard et al, 2012). In addition, specialist remodelers, such as the Snf2-like remodeler Helicase, lymphoid specific (HELLS), appear to enable HDR at some heterochromatic regions (Kollarovic et al, 2019) and heterochromatin-resident proteins such as HP1 and Sentrin/SUMO-Specific Protease SENP7 (SENP7) nevertheless facilitate HDR (Garvin et al, 2013; Lee et al, 2013). A recent study using CRISPR-Cas9 to quantify HDR- and NHEJ-derived gene editing events at single-target sequences subjected to distinct chromatin conformations found that NHEJ and not HDR was more sensitive to chromatin state.…”
Section: Chromatin Barriers To Resectionmentioning
confidence: 99%